Updated data on the epidemiology of Inflammatory Bowel Disease (IBD) in Lebanon - Antoine Abou Rached; Joyce Saniour; Antoine Geagea; Christian Salameh; Souheil Hallit; Charbel Yazbeck (PLoS ONE, 2026)
Objective The objective of the study was to review available data on IBD in Lebanon based on histopathological reports and endoscopic data to identify the number of newly diagnosed cases per year, age, gender, and disease phenotype, and subsequently update the incidence and prevalence of the disease. Methods A review of all histopathological reports of newly diagnosed IBD patients over a 20-year period was conducted, along with a review of available clinical and endoscopic information at the National Institute of Pathology. The clinical data analysed included the type of IBD, age, gender, number of cases diagnosed per year, location of each IBD type and disease progression over time. The Montreal classification for age and phenotype was applied to both diseases. Results Over a 20-year period (from January 2000 to December 2020), 2,869 IBD patients (1,365 with Crohn’s disease (CD) and 1,504 with ulcerative colitis (UC) were included. Our sample represents 20% of the Lebanese population with IBD. No cases of unclassified IBD were identified since all patients were followed up throughout the years. The male-to-female ratio was 1.15 for UC patients and 1.3 for CD patients. The average age was 41 years for UC and 36.4 years for CD. Ileal involvement and left-sided colonic involvement were the most frequently noted in CD and UC, respectively. A progressive increase in diagnosed cases of CD and UC was observed over this 20-year period. The annual incidence rose from 4.9 to 11 per 100,000, with a cumulative incidence of 6.53 per 100,000 and a prevalence of 130.56 per 100,000. The highest incidence occurred between ages 21–30. Incidence trends were independently predicted by age group and calendar period, with markedly higher rates among individuals aged 20–39 and 40–59 years with a significant increase in the 2015–2020 period, whereas sex and disease type showed no significant associations. Conclusion Epidemiological data demonstrated a progressive increase in the incidence of IBD over this 20-year period, with a slight male predominance. Ileal involvement is predominant in CD, whereas involvement extending beyond the splenic flexure is present in more than half of UC cases.